Drift‐corrected seafloor pressure observations of vertical deformation at Axial Seamount 2013–2014. Issue 9 (27th September 2016) - Sasagawa, G.; Cook, M. J.; Zumberge, M. A.
Abstract: Axial Seamount on the Juan de Fuca Ridge is a site of ongoing volcanic activity. The vertical component of the deformation can be observed with ambient seawater pressure gauges, which have excellent short‐term resolution. However, pressure gauge drift adds additional and significant uncertainty in estimates of long‐period deformation; drift rates equivalent to 20–30 cm/yr have been observed. One way to circumvent gauge drift is to make differential pressure measurements relative to a distant and presumably stable seafloor reference site. Such measurements require a remotely operated vehicle and can only be made infrequently. Another approach is to incorporate a piston gauge calibrator in the seafloor pressure recorder to generate an in situ reference pressure that, when periodically applied to the drift‐susceptible gauge, can be used to determine and remove gauge drift from the time series. We constructed a self‐calibrating pressure recorder and deployed it at Axial Seamount in September 2013. The drift‐corrected record from that deployment revealed an uplift of the volcano summit of 60 cm over 17 months. Key Points: An instrument was deployed on Axial Seamount to detect seafloor vertical deformation by observing pressure from constantly calibrated gauges Uplift of the volcano was detected, and the gauge drift correction was significant